Nonalcoholic Steatohepatitis Score is an Independent Predictor of Right Ventricular Dysfunction in Patients with Nonalcoholic Fatty Liver Disease - SÜNBÜL, MURAT; ERGELEN, RABİA; YILMAZ, YUSUF (WILEY-HINDAWI, 2015)
ObjectiveNonalcoholic fatty liver disease (NAFLD) is associated with increased risk of cardiovascular disease and impaired left ventricular (LV) function, yet the impact of NAFLD on right ventricular (RV) function remains unclear. We investigate the RV functional properties in patients with NAFLD. MethodsNinety consecutive patients with the diagnosis of biopsy-proven NAFLD and 45 age- and sex-matched controls were included. All patients underwent an echocardiographic examination. RV function was evaluated by two-dimensional (2D) speckle-tracking echocardiography (STE). ResultsMean fibrosis stage and nonalcoholic steatohepatitis (NASH) scores were 1.31.1 and 5.2 +/- 1.6, respectively. NAFLD patients displayed decreased RV function compared to controls. NAFLD patients with liver fibrosis (67 patients) had significantly lower RV function assessed by GLS (global longitudinal strain) compared to patients without liver fibrosis (18.9 +/- 3.4% vs. 21.6 +/- 2.3%, P<0.001). NASH score 5 was associated with lower RV-GLS (18.9 +/- 3.1% vs. 21.0 +/- 3.4%, P=0.006). NASH score inversely correlated with RV-GLS (r=-0.370, P<0.001) such as patients with impaired RV-GLS (<19%) showed significantly higher NASH score compared to normal RV-GLS group (5.8 +/- 1.4 vs. 4.8 +/- 1.7, P=0.009). Logistic regression analysis revealed that NASH score was an independent predictor of impaired RV function in patients with NAFLD. ConclusionsPatients with NAFLD have impaired RV function. NASH score inversely correlates with RV-GLS and independently predicts impaired RV function in patients with NAFLD.
Keywords: nonalcoholic fatty liver disease; Right ventricular function; speckle-tracking echocardiography; SPECKLE TRACKING ECHOCARDIOGRAPHY; METABOLIC SYNDROME; DEFORMATION PARAMETERS; DIASTOLIC DYSFUNCTION; LOGISTIC-REGRESSION; CARDIOVASCULAR RISK; NATURAL-HISTORY; SAMPLE-SIZE; THICKNESS; DESIGN